Sistem Pendukung Keputusan Keluarga Penerima Manfaat Bantuan Langsung Tunai Dana Desa (BLT-DD) - Kusuma Safitri, Lestari; Jasmir , Jasmir (LPPM Universitas Dinamika Bangsa, 2023)
Village Fund Direct Cash Assistance is the government's effort to stabilize the economy of the poor in Indonesia, especially in villages. collectively and as social protection for the community. The purpose of this study was to design and apply a decision support system to help determine a decision for the Village Head of Bukit Tempurung to determine the prospective beneficiary families of the Village Fund Direct Cash Assistance (BLT-DD). This study uses a research method using SAW (Simple Addictive Weight). This research will produce a ranking of each alternative. Based on the research that has been done, there are still difficulties because the assessment is still done subjectively. This study uses UML (Unified Modeling Language) tools in the form of use case diagrams and activity diagrams. With this decision support system it can help minimize errors, because the determination is based on predetermined criteria and has gone through a calculation process so that the assessment is objective